2000
DOI: 10.2214/ajr.175.4.1750997
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Disease

Abstract: Compared with sonography, CT venography in addition to CT pulmonary angiography is a relatively accurate method for evaluation of femoropopliteal venous thrombosis. Combined CT pulmonary angiography and CT venography may be more efficacious than sonography or two separate examinations in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Since the advent of MDCT, the diagnostic ability of CT venography to detect DVT in the lower extremities was reported to be comparable to Doppler sonography (30-32). These findings were mainly based on the significant difference in attenuation between the deep vein and the perivenous muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the advent of MDCT, the diagnostic ability of CT venography to detect DVT in the lower extremities was reported to be comparable to Doppler sonography (30-32). These findings were mainly based on the significant difference in attenuation between the deep vein and the perivenous muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of an isolated calf vein DVT as the cause of a clinically important pulmonary embolism or persistent lower extremity symptoms has been a subject of considerable debate in the medical literature (30). According to Wang et al, a calf vein DVT after TKA disappears spontaneously with time (12).…”
Section: Discussionmentioning
confidence: 99%
“…In this method, known as combined CTA and CTV, following pulmonary CTA applied for PE, 3-5 min after starting the injection of contrast dye, the venous system between the diaphragm and the popliteal area is scanned at 5-10 mm slice thickness and 1-5 cm slice intervals [2, 6]. Different studies have reported sensitivity of this method in respect of DVT as 89-100% and specificity as 94-100% [2, 6, 10]. …”
Section: Discussionmentioning
confidence: 99%
“…CT venography in addition to CT pulmonary angiography is a relatively accurate method for evaluation of femoropopliteal venous thrombosis. In a comparative study between CTA-CTV and sonography, Garg et al [53] found a 100% sensitivity, 97% specificity, 100% negative predictive value, and 71% positive predictive value for CTV. Satisfactory or good quality CT venography examination was obtained in 97% of the studies.…”
Section: Computerized Tomography Angiography and Venographymentioning
confidence: 99%